Diagnosis and localization of parathyroid adenomas using 16‐slice SPECT/CT: A clinicopathological correlation. Issue 5 (21st September 2021) - Sankaran, Sharanya J; Davidson, Jennifer
Abstract: Introduction: This study aimed to evaluate a new 16‐slice SPECT/CT scanner at Auckland City Hospital for its use in the detection and localization of parathyroid adenomas in patients with primary, secondary and tertiary hyperparathyroidism. The secondary outcome was to compare findings from SPECT/CT with ultrasound and operative findings. Methods: One hundred patients who underwent a SPECT/CT scan for primary/secondary/tertiary hyperparathyroidism were included in this study. Of these patients, 45 received surgery. SPECT/CT and ultrasound findings were collated for each patient, and of those who received surgery, operative and pathological findings were compared with those on SPECT/CT. Results: The sensitivity of diagnosis and localization was 86.5% (95% CI: 71.2–95.5%). Specificity was 25.0% (95% CI: 3.2–65.1%). Comparison between SPECT/CT and ultrasound findings demonstrated a kappa coefficient of 0.203 (95% CI: −0.036 to 0.442), correlating with fair agreement. These figures are in line with other published series. Conclusion: The SPECT/CT scanner (and associated reporters) at Auckland City Hospital demonstrates high sensitivity in the detection and localization of parathyroid adenomas and is an effective first‐line investigation in patients with primary/secondary/tertiary hyperparathyroidism.